Dihydropyrimidine dehydrogenase testing prior to treatment with 5-fluorouracil, capecitabine, and tegafur: a consensus paper - Wörmann, Bernhard; Bokemeyer, Carsten; Burmeister, Thomas; Köhne, Claus-Henning; Schwab, Matthias; Arnold, Dirk; Blohmer, Jens-Uwe; Borner, Markus; Brucker, Sara; Cascorbi, Ingolf; Decker, Thomas; de Wit, Maike; et al. (Oncology research and treatment, 2020)
Background: 5-Fluorouracil (FU) is one of the most commonly used cytostatic drugs in the systemic treatment of cancer. Treatment with FU may cause severe or life-threatening side effects and the treatment-related mortality rate is 0.2-1.0%. Summary: Among other risk factors associated with increased toxicity, a genetic deficiency in dihydropyrimidine dehydrogenase (DPD), an enzyme responsible for the metabolism of FU, is well known. This is due to variants in the DPD gene (DPYD). Up to 9% of European patients carry a DPD gene variant that decreases enzyme activity, and DPD is completely lacking in approximately 0.5% of patients. Here we describe the clinical and genetic background and summarize recommendations for the genetic testing and tailoring of treatment with 5-FU derivatives. The statement was developed as a consensus statement organized by the German Society for Hematology and Medical Oncology in cooperation with 13 medical associations from Austria, Germany, and Switzerland. Key Messages: (i) Patients should be tested for the 4 most common genetic DPYD variants before treatment with drugs containing FU. (ii) Testing forms the basis for a differentiated, risk-adapted algorithm with recommendations for treatment with FU-containing drugs. (iii) Testing may optionally be supplemented by therapeutic drug monitoring.